UM SIMPLES SENSOR DE ÓXIDO DE GRAFITE MODIFICADO COM BENTONITA PARA QUANTIFICAÇÃO DE 17β-ESTRADIOL - TRENKEL, Fernanda Adriéli; RODRIGUES, Lucas Limeira; FIORUCCI, Antonio Rogerio; ARRUDA, Gilberto José (ANAIS DO ENIC, 2023)
-